Pengaruh Bantuan Langsung Tunai (Bsm) Dan Motivasi Terhadap Kualitas Pendidikan di Kabupaten Tulungagung - Hudiyanto, Wahyu; Mega Hastuti, Sri Wahyuni (Universitas Islam Kadiri, 2024)
This research aims to: Analyzing the simultaneous significant effects of nalyzing the simultaneous effects of variables on the quality of education, analyzing the influence of motivation on the quality of education; determining which variable, either asistence for poor students or motivation, is more dominant in influencing the quality of education. This research uses Descriptive Quantitative. the population all first-grade students in publick/private school in Tulunggaung Regency. The sample for this study is 10% of the total population, which is 635 people. The technique is a method of data collection now. In this study, researchers used the software (software), Microsoft Office Excel 2007 to carry out a descriptive and statistical analysis software (software) Statistical Package for Social Sciences (SPSS) for Windows version 21.0 to carry out the test, test the classical, hypothesis testing and multiple linear regression analysis, , The research findings indicate a significant influence betwen the variables of direct cash assistence (BSM), nd motivation on the quality of education in Tulungagung regency